2017
DOI: 10.1099/mic.0.000493
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and biochemical characteristics of the inulosucrase HugO from Streptomyces viridochromogenes DSM40736 (Tü494)

Abstract: Polyfructans are synthesized from sucrose by plants (mostly inulin) and by both Gram-negative and Gram-positive bacteria (mostly levan). In the phylum Actinobacteria only levan synthesis by Actinomyces species has been reported. We have identified a putative fructansucrase gene (hugO) in Streptomyces viridochromogenes DSM40736 (Tü494). HugO was heterologously expressed and biochemically characterized. HPSEC-MALLS and 2D-1H-13C nuclear magnetic resonance (NMR) spectroscopy analysis showed that the fructan polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…Inulosucrase has been identified in only a few bacterial species such as Leuconostoc citreum , 13 Lactobacillus reuteri , 14 Lactobacillus johnsonii , 15 Lactobacillus gasseri , 16–18 and Streptomyces viridochromogenes . 19 Structural analysis shows that bacterial inulosucrases have low structural similarity when compared to fungal β-fructofuranosidase. In contrast, they are closely related to levansucrase (E.C.…”
Section: Introductionmentioning
confidence: 99%
“…Inulosucrase has been identified in only a few bacterial species such as Leuconostoc citreum , 13 Lactobacillus reuteri , 14 Lactobacillus johnsonii , 15 Lactobacillus gasseri , 16–18 and Streptomyces viridochromogenes . 19 Structural analysis shows that bacterial inulosucrases have low structural similarity when compared to fungal β-fructofuranosidase. In contrast, they are closely related to levansucrase (E.C.…”
Section: Introductionmentioning
confidence: 99%
“…Crude InuGB-V3 exhibited rapid sucrose conversion at a broad pH spectrum (pH 3.5-6.0) while increased sucrose hydrolysis was observed at lower pH values. A pH optimum in the slightly acidic to neutral range was shown for many inulosucrases originating from lactic acid bacteria (Olivares-Illana et al 2002;Hijum et al 2002;Anwar et al 2008Anwar et al , 2010Ni et al 2018Ni et al , 2020, as well as for inulosucrases from Streptomyces viridochromogenes (Frasch et al 2017), Streptococcus mutans (Heyer et al 1998), and Bacillus macerans (Kim et al 1998). In addition, Ni et al (2018) showed for a variant of the inulosucrase from L. gasseri that the hydrolysis ratio increased at pH values below optimum.…”
Section: Discussionmentioning
confidence: 99%
“…Inulosucrase (E.C. 2.4.1.9) is a fructosyltransferase, which is found in bacterial species such as Leuconostoc citreum, Lactobacillus reuteri, Lactobacillus johnsonii, Lactobacillus gasseri, and Streptomyces viridochromogenes . This enzyme converts sucrose to inulin-type fructooligosaccharide (IFOS) and β-2,1 fructan, a well-known prebiotic used in the food and pharmaceutical industries.…”
Section: Introductionmentioning
confidence: 99%